The Impact of QRIS on Consumer Behavior in Urban Areas - Asa, Ringga Sentagi; Shabrina, Fildzah (CV. Civiliza Publishing, 2025)
The purpose of this study is to study how urban consumer behavior is influenced by the implementation of digital payment systems, specifically the Quick Response Code Indonesian Standard (QRIS). This study used a quantitative approach, sending questionnaires to respondents in urban areas. The research results show that QRIS usage and ease of access influence consumer behavior. Key findings indicate that people purchase more frequently, are more likely to engage in consumer behavior, and prefer cashless payments. Due to the convenience of QRIS, 62% of respondents reported making more impulse purchases. In addition, consumers' perceptions of the practicality and security of QRIS also help them prefer to use it. The majority of respondents considered QRIS secure (76%) and faster than cash payments (84%). This research shows that QRIS implementation not only increases the speed and convenience of transactions but also has socio-economic consequences, such as an increased propensity to spend more money in urban areas.